Potential of lindur flour (Bruguiera gymnorrhiza) for gluten-free cookies (Kulinur) as an alternative snack for children with autism spectrum disorder - Hidayatusy Syukrina Puteri; Adhi Nurhartanto; Yunita Dinda Dewi (AcTion: Aceh Nutrition Journal, 2026)
Autism Spectrum Disorder (ASD) affects about 2.4 million individuals in Indonesia, with 500 new cases annually. Children with ASD often experience gluten and casein intolerance, leading to a restricted diet and inadequate protein and carbohydrate intakes. Lindur flour (Bruguiera gymnorrhiza), containing 2.57–2.68% protein and 80–82% carbohydrates, may serve as a local gluten-free substitute for wheat flour. This quasi-experimental study used a Completely Randomized Design (CRD) with five formulations (F0–F4) combining lindur and modified cassava (mocaf) flours. Proximate composition, gluten content (ELISA), and sensory attributes were analyzed in duplicate and evaluated using one-way ANOVA (p<0.05) and the Kruskal–Wallis test. Increasing the substitution of lindur significantly affected the moisture, ash, protein, fat, crude fiber, and carbohydrate contents. The 100% lindur formulation (F4) exhibited the highest protein (11.54%) and fiber (7.82%) contents, whereas all products were gluten-free (<3 ppm). Sensory evaluation indicated that formulations with 25–50% lindur flour (F1–F2) achieved the highest acceptability in terms of taste, texture, and overall preferences. This study is the first to utilize lindur flour in gluten-free cookie development for children with ASD, demonstrating its potential as a nutritious, locally sourced ingredient for functional food innovation in gluten-free diets